SISTEM IDENTIFIKASI MENGGUNAKAN RFID DAN SENSOR INFRARED BERBASIS IOT TERHADAP PENGEMBANGAN KAMPUS PINTAR - Nazuarsyah, Nazuarsyah; Muzakir, Ully; Mukhroji, Mukhroji; Ginting, Rossiana; Munadi, Rizal (UIN Ar-Raniry, 2023)
This study aims to discuss the development of an identification system tool to unlock doors using Radio Frequency Identification (RFID) and infrared sensors based on the Internet of Things (IoT). This research model is the development of prototyping, consisting of several stages, namely the needs analysis stage through interviews with lecturers and education staff, and conducting literature studies on previous research to get more information on this research. The design and design phase of the tool consists of RFID, infrared sensor, relay, and I2C LCD connected to microcontroller. The solenoid lock is connected directly to the relay as output. The test results on the hardware and software side, the average response time of the device to unlock from outside the room using RFID is 1.13 seconds, while the average response time of the tool to unlock from inside the room using infrared is 0.77 seconds. Thus, the results of this study found the average response time of infrared sensors is faster by 0.09 seconds than RFID. This system can be further developed using other access media such as bluetooth devices that are easily found in smartphones.